2016
DOI: 10.1159/000452564
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Suppresses IL-23 Production in Human Dendritic Cells via an AMPK-Dependent Pathway

Abstract: Background/Aims: Cilostazol has been previously demonstrated to inhibit IL-23 production in human synovial macrophages via a RhoA/ROCK-dependent pathway. However, whether cilostazol affects IL-23 production in human dendritic cells remains largely unknown. The present study was designed to investigate this question and elucidate the possible underlying mechanisms. Methods: Human monocyte-derived dendritic cells (mo-DCs) were pretreated with or without cilostazol and then incubated with zymosan. Enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…[ 39 ] Shi et al have observed that cilostazol has an anti‐inflammatory effect via AMPK activation in human dendritic cells. [ 40 ] Also, Lee et al have shown that cilostazol inhibits alcohol‐induced apoptosis through AMPK activation. [ 32 ] Similarly, in our work, cilostazol elevated AMPK phosphorylation, but, it did not affect the effect of meloxicam in combination drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 39 ] Shi et al have observed that cilostazol has an anti‐inflammatory effect via AMPK activation in human dendritic cells. [ 40 ] Also, Lee et al have shown that cilostazol inhibits alcohol‐induced apoptosis through AMPK activation. [ 32 ] Similarly, in our work, cilostazol elevated AMPK phosphorylation, but, it did not affect the effect of meloxicam in combination drug.…”
Section: Discussionmentioning
confidence: 99%
“…Based on meloxicam and cilostazol IC50 concentrations, different concentrations (20,40,60, and 80 µM) of combination drugs were prepared and stored at −4°C. Next, the MTT assay was performed as described above.…”
Section: Combination Drug Preparation and Synergism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies indicated that Zymosan-A can induce NF-κB phosphorylation and nuclear translocation by targeting TLR2[21, 22, 29]. Zymosan-A can also upregulate cytokines, including TNF-α; the IL-1 family; the IL-6, IL-8, and IL-10 family; IL-11; IL-23; the IL-12 family; IL-15; TGF-β; and G-CSF[30-34]. In addition, IL-6, IL-11, IL-12, G-CSF, and TNF-α are regarded as radiation protection factors [35-40].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, AMPK activation can suppress the production of IL-23 in human mo-DCs (Shi et al, 2016) and MEK1/2-ERK1/2-AMPK signaling axis participated in promoting survival of mDCs, suggesting that AMPK may be a potential target to modulate mDC lifespan and the immune response (López-Cotarelo et al, 2015).…”
Section: Ampk and DCmentioning
confidence: 99%